A study of the vegetative development of Amaranthus in order to integrate it into agricultural technologies and adapt it to climatic conditions from Somesan Plateau - George Sergiu; Vladimir Paul; Pascal Balint; Ludovic Bentoiu; Drăgoi Nicolae Bretan (African Journal of Environmental Economics and Management, 2014)
The AMARANTHUS species are cultivated as “pseudo cereals” because of their high content of carbohydrates, proteins and fats, comparable or even superior to cereals. In this backdrop, the present study aims to test the vegetative development of AMARANTHUS cultivars, in order to integrate the research results with the agricultural technologies, adapted to the climatic conditions from Somesan Plateau. The cultivars tested were: Alegria, Amont, Pleisman, Golden, Mercado, Burgundi, Hopi Red Dye, Chihuahn, Opopeo, MT3 (parent material of the cultivar Amont), Plenitude and Intense Purpure. The results obtained in seed production of the AMARANTHUS cultivars shows very significant positive production of variants with densities of 100,000 plants/ha. Interaction of the cultivars of AMARANTHUS upon density is much more diversified on the yields obtained and shows in case of density 70,000 plants/ha superiority of the cultivars: Alegria, Amont, Golden and Plenitude, and in case of 100,000 plants/ha cultivars: Amont, Golden, Hopi Red Dye, Plenitude and Intense Purpure. Influence of variety of AMARANTHUS on biomass production shows the cultivars with the highest productivity as follows: Plenitude, Alegria, Amont, Intense Purpure. Influence of density on biomass productivity of AMARANTHUS is similar with the seeds productivity, namely 100,000 plants/ha provides very significant positive production compared with the average of the variants.